The Intersection of Modern Islam, Digital Literacy, and Childhood Education: A Systematic Literature Review of Madrasah-Based Educational Trends in Indonesia (2008–2026) - Mukaromah, Ning; Syawaludin, Makhfud; Aziz, Abd.; Arshad, Imran (Jurnal Pendidikan Anak, 2025)
In the era of digital transformation, the integration of technology into modern Islamic education is crucial, as the sociological dynamics of communication in Indonesian madrasas undergo a fundamental shift from conventional patterns to digital-based interactions. This study aims to evaluate the impact of digital learning on the dynamics of social communication in madrasa environments and identify sociological factors that influence the effectiveness of such technology integration. A Systematic Literature Review (SLR) method combined with a meta-analysis approach was conducted on 456 scientific articles sourced from the Scopus database between 2008 and 2026. Of these, 35 final articles were selected based on inclusion criteria for effect size analysis. Data analysis was conducted using Random Effects Model estimation—given the heterogeneity between studies (I^2 > 50%)—and the Cochrane Q test using JASP v.0.18 software. The results showed a significant positive impact and were in the high category (d = 0.82) on the effectiveness of social communication and student participation in madrasas. Visualization through a funnel plot showed a symmetrical data distribution, indicating low publication bias in the analyzed literature. These findings also revealed that moderating variables, such as teacher digital competence and technological infrastructure support, are key determinants in the successful adoption of digital learning. The implications of this study emphasize the need for reconstruction of the Islamic education curriculum that aligns the values ​​of Islamic moderation (Wasathiyah) with digital communication skills to strengthen the resilience of madrasa communities in the digital era. Specifically for Islamic basic education, collaboration with parents is needed in digital security.